Arterial blood gases in emergency medicine: how well do our registrars and consultants currently enrolled in the Western Cape Division of Emergency Medicine interpret them - Xafis, Paul (Stellenbosch : Stellenbosch University, 2017)
Thesis (MMed)--Stellenbosch University, 2014.